Integration of Islamic Values Into Balanced Scorecard As A Strategic Management System at A Sharia Hospital - Nur Hidayah; Arlina Dewi; Gofur Ahmad; Suhendar Sulaeman (School of Business, Bogor Agricultural University (SB-IPB), 2024)
Background: A Sharia Hospital in Central Java of Indonesia had previously used a balanced scorecard (BSC) to assess hospital performance. However, BSC has not been integrated into the hospital's strategic management process. Purpose: This study aims to develop a Sharia Hospital’s strategic plan by adopting a BSC integrated into Islamic values. Design/methodology/approach: A qualitative study was conducted involving a Strengths, Weaknesses, Opportunities, and Threats (SWOT) analysis with 10 respondents and focus group discussions with 11 strategic planning teams.Findings/Result: The results indicate that the hospital has completed several stages of developing a strategic plan, including defining the hospital's vision and mission, conducting a SWOT analysis, and formulating strategic objectives. Moreover, BSC has been implemented into the hospital's strategic planning process, particularly in formulating strategic objectives aligned with Islamic values. This reveals that the BSC has been integrated into the hospital’s strategic management process.Conclusion: The result of this study provides a reference for a Sharia Hospital to adopt BSC aligned with Islamic values in the preparation of a hospital strategic plan. By integrating Islamic values into BSC, the hospital can formulate and implement strategies and evaluate the hospital's performance more comprehensively and measurable, covering financial and non-financial performance while promoting Islamic values.Originality/value (State of the art): Developing a strategic plan using the BSC is commonly conducted, but integrating Islamic values into the BSC perspective is still relatively uncommon. Hence, this study contributes significantly to hospital strategic management practices, particularly in Sharia hospitals. Keywords: balanced scorecard, hospital management, Islamic values, sharia hospital, strategic management